Tubulocystic renal cell carcinoma is an entity that is immunohistochemically and genetically distinct from papillary renal cell carcinoma. Issue 6 (21st October 2015) - Tran, Thu; Jones, Carol L; Williamson, Sean R; Eble, John N; Grignon, David J; Zhang, Shaobo; Wang, Mingsheng; Baldridge, Lee Ann; Wang, Lisha; Montironi, Rodolfo; Scarpelli, Marina; Tan, Puay‐Hoon; et al.
Abstract : Aims: Some studies have suggested that tubulocystic carcinoma may be related to papillary renal cell carcinoma. We sought to compare and contrast the molecular and immunohistochemical profiles of tubulocystic carcinoma with those of papillary renal cell carcinoma. Methods and results: Twelve cases of pure tubulocystic renal cell carcinoma were subjected to fluorescence in‐situ hybridization assessment of chromosomal number for chromosomes 7 and 17, and for TFE3 translocation. Immunohistochemical labelling for AMACR, p63, cytokeratin 7, PAX8, cytokeratin 20 and carbonic anhydrase IX was assessed in all tumours. No tumour showed gains of chromosomes 7 or 17, or TFE3 translocation by fluorescence in‐situ hybridization. Immunohistochemistry revealed all tumours to be non‐reactive with antibodies against p63 and cytokeratin 20. Conversely, the antibody against AMACR gave a positive reaction in the neoplastic cells of all tumours. Four tumours showed focal labelling with antibody against carbonic anhydrase IX, and five tumours showed focally positive reactions with antibody against cytokeratin 7. Recurrence and metastatic disease were not found for the patients with available follow‐up information. Conclusions: Pure tubulocystic renal cell carcinoma is an indolent tumour with a good prognosis. Our data support the distinction of this neoplasm as a separate entity.